Innovation in the Public Library: where we are and where we go - García Gómez, F. Javier (Revista General de Información y Documentación, 2013)
Innovation, a key element in the current historical moment, it primoridal for all institutions face up to the challenges guarantees they face. Generally, these innovation processes are based primarily on the technological component, although it is possible to innovate with other resources, approaches, and service approaches. Innovation also is becoming one of the hallmarks of Spanish public libraries. These institutions mainly innovate from available technology offering personalized and adapted according to the needs and interests of its user community. It analyzes some paradigmatic cases of innovative services in Spanish public libraries
Keywords: Public Libraries; Innovation; Technological Innovation; Creativity; Spain; Community Services / Internet Based Services